2022
DOI: 10.5455/jcmr.2022.13.05.04
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Female Patients Towards HPV Vaccine and Pap Smear at Maternity and Children Hospital in the City of Makkah, Saudi Arabi

Abstract: Cervical cancer is one of the leading life-threatening cancers around the globe. In fact, it is the fourth most common reported cancer in women with an estimate of 530,000 cases every year. In Saudi Arabia, a recent report from the Human papilloma virus (HPV) information centre has indicated annual cases of 358 diagnosed cervical cancer, placing it as the eighth most frequent cancer in the country. Such disease has been found to have a strong association with HPV infection as the primary risk factor. HPV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Understanding the knowledge and perceptions of this population is essential for tailored interventions that address cultural and religious factors influencing HPV vaccination decisions. Studies conducted at Makkah City's Maternity and Children Hospital revealed surprisingly low awareness among participants regarding HPV vaccination and Pap smears despite high levels of awareness about cervical cancer [2]. The findings suggest a potential gap in communication and education provided by healthcare providers in Makkah City, emphasizing the significance of further investigating healthcare professionals' practices and recommendations related to HPV vaccination.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Understanding the knowledge and perceptions of this population is essential for tailored interventions that address cultural and religious factors influencing HPV vaccination decisions. Studies conducted at Makkah City's Maternity and Children Hospital revealed surprisingly low awareness among participants regarding HPV vaccination and Pap smears despite high levels of awareness about cervical cancer [2]. The findings suggest a potential gap in communication and education provided by healthcare providers in Makkah City, emphasizing the significance of further investigating healthcare professionals' practices and recommendations related to HPV vaccination.…”
mentioning
confidence: 85%
“…affect women between the ages of 15 and 44 [2]. The incidence of cervical cancer has been on the rise, with late-stage diagnoses complicating treatment and contributing to elevated morbidity and mortality rates [2,4].…”
mentioning
confidence: 99%
See 3 more Smart Citations